2019
DOI: 10.1002/cphc.201900314
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Reduction by Hydrogen Pre‐Reduced Acceptor‐Doped Ceria

Abstract: The reactivity of H2 pre‐reduced acceptor‐doped ceria materials Gd0.10Ce0.90O2‐δ (GDC10) and Sm0.15Ce0.85O2‐δ (SDC15) was tested with respect to the reduction of CO2 to CO in the context of the reverse water‐gas shift reaction. It was demonstrated that not only oxygen vacancies, but also dissolved hydrogen is a reactive species for the reduction of CO2. Dissolved hydrogen must be considered upon discussion of the mechanism of the reverse water‐gas shift reaction on ceria‐derived materials apart from oxygen vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the region between 2200 and 1150 cm −1 , the observed bands are mainly due to the interaction of CO 2 with the CeO 2 surface. It is important to emphasize that pre-reduction up to 500 • C guarantees a Ce 3+ containing layers (surface-subsurface), as evidenced by a negative, although not very intense, peak at 2114 cm −1 corresponding to the Ce 3+ transition, a phenomenon also observed on CeO 2 solid solutions with aliovalent elements, such as Gd 3+ or Sm 3+ by M. Grünbacher et al [54]. At 200 • C, intense bands appeared at 1612, 1390, and 1216 cm −1 assigned to the ν a (CO 3 ), ν s (CO 3 ) and δ(OH) vibrations of bicarbonate species chemisorbed on reduced CeO 2 [12,52,55,56].…”
Section: Driftmentioning
confidence: 82%
“…In the region between 2200 and 1150 cm −1 , the observed bands are mainly due to the interaction of CO 2 with the CeO 2 surface. It is important to emphasize that pre-reduction up to 500 • C guarantees a Ce 3+ containing layers (surface-subsurface), as evidenced by a negative, although not very intense, peak at 2114 cm −1 corresponding to the Ce 3+ transition, a phenomenon also observed on CeO 2 solid solutions with aliovalent elements, such as Gd 3+ or Sm 3+ by M. Grünbacher et al [54]. At 200 • C, intense bands appeared at 1612, 1390, and 1216 cm −1 assigned to the ν a (CO 3 ), ν s (CO 3 ) and δ(OH) vibrations of bicarbonate species chemisorbed on reduced CeO 2 [12,52,55,56].…”
Section: Driftmentioning
confidence: 82%
“…All samples got a sharp peak at about 90 C, which was attributed to desorption of weak-bonded bicarbonate (Keturakis et al, 2014). Smooth peaks at 370 C and 550 C, which originated from desorption of monodentate carbonate (weak basic site) and polydentate carbonate (strong basic site), respectively (Ewald and Hinrichsen, 2019;Grü nbacher et al, 2019;Zheng et al, 2019), appeared in L-Ni/g-Al 2 O 3 . The intensity of these two peaks intensified with Ni loading and a new desorption peak at 500 C appeared, which was possibly derived from a kind of bidentate carbonate (Busca and Lorenzelli, 1982 (Ewald and Hinrichsen, 2019).…”
Section: Operando Raman and In Situ Driftsmentioning
confidence: 99%
“…A low activation energy of 36 ± 4 kJ/kmol for the oxygen regeneration of ceria was previously reported by Bulfin et al [69], which is compatible with the observed low effect of reaction temperature on kinetics. On the other hand, the mechanism of CeO2 regeneration through H2O or CO2 oxidation has been observed to involve the formation of hydride, hydroxyl, and carbonate species [70][71][72][73]. 1.0 ± 0.1 1.2 ± 0.2 1.44 ± 0.05 The easiness of regeneration, together with a carrier reduction close to the theoretical values, makes ceria a suitable OC to conduct repeated cycles, while 950 °C may be identified as the best operating temperature as it represents a reasonable trade-off between rapid reforming kinetics, carbon deposition, and energy penalties.…”
Section: Chemical Looping Testsmentioning
confidence: 99%